Titanium-magnesium layered composite metal material and method for manufacturing the same

CN119749041BActive Publication Date: 2026-10-23EAST CHINA UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510073658.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2026-10-23
Estimated Expiration
2045-01-17

AI Technical Summary

Technical Problem

[0004]为了解决上述现有技术中的钛镁层状复合金属材料制备技术中材料不均匀、结合不好导致塑性差、界面处缺陷杂质多等问题,本发明提供一种钛镁层状复合金属材料及其制备方法

Benefits of technology

[0015]本发明的纯钛板和镁合金板通过交替叠层、真空热压和热轧等步骤制成钛镁层状复合金属材料,高塑性,长寿命,致密性好且界面处无明显脆性金属间化合物。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119749041B_ABST
    Figure CN119749041B_ABST
Patent Text Reader

Abstract

The application relates to a preparation method of a titanium-magnesium laminated composite metal material, which comprises the following steps: respectively pretreating pure titanium plates and magnesium alloy plates; alternately stacking the pure titanium plates and the magnesium alloy plates to form a stacked structure with the pure titanium plates located at the outermost layers; under the conditions of a temperature of 500 DEG C to 600 DEG C and a pressure of 5 MPa to 20 MPa, the stacked structure is subjected to hot-pressing compounding to form a pre-bonding block; under the condition of a temperature of 400 DEG C to 500 DEG C, the pre-bonding block is subjected to rolling compounding to form a composite structure; and under the condition of a temperature of 350 DEG C to 500 DEG C, the composite structure is subjected to annealing treatment to form the titanium-magnesium laminated composite metal material. The application also relates to the titanium-magnesium laminated composite metal material prepared by the above method. The pure titanium plates and the magnesium alloy plates are stacked alternately, vacuum hot-pressed and hot-rolled to form the titanium-magnesium laminated composite metal material, which has high plasticity, long service life, good compactness and no obvious brittle intermetallic compound at the interface.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the preparation of composite materials, and more specifically to a titanium-magnesium layered composite metal material and its preparation method. Background Technology

[0002] Titanium, magnesium, and their alloys are widely used lightweight metallic materials in engineering. Titanium, in particular, is widely used in aerospace, medical, and marine fields due to its high strength-to-weight ratio, high corrosion resistance, biocompatibility, and non-toxicity and non-magnetic properties, which have attracted considerable attention. However, its high production cost and processing difficulty limit its applications. Magnesium is one of the lightest metallic structural materials, and its high strength and rigidity, excellent machinability, high damping and vibration reduction properties, and easy recyclability have led to its application in aerospace, electronics, and military fields. However, magnesium and its alloys are severely limited by their susceptibility to corrosion, flammability, and poor plastic deformation capacity. Therefore, combining titanium and magnesium to prepare titanium-magnesium layered composite materials with superior bonding properties will combine the advantages of both metals—lightweight, corrosion-resistant, and highly malleable—with the high plasticity and long lifespan of layered composite materials, showing broad application prospects in aerospace, electronics, marine engineering, and military industries.

[0003] In the field of materials science, the bonding of titanium and magnesium faces a series of challenges. First, these two metals differ significantly in their physicochemical properties; they exhibit low miscibility in the solid state and are difficult to form stable intermetallic compounds. Furthermore, during processing, both titanium and magnesium readily react with oxygen to form oxide layers, further hindering direct bonding. Due to these factors, the bonding process of titanium and magnesium faces significant technical challenges. Currently, common preparation processes for titanium-magnesium composites include explosive welding, rolling composite, and powder metallurgy. Explosive welding offers high production efficiency but suffers from numerous defects at the weld joint, affecting material properties and posing safety hazards. Powder metallurgy allows for precise control of composition and good material forming, but its low production efficiency and tendency to generate porosity make it a primary method for preparing layered composite materials. Rolling composite, due to its high production efficiency, good forming properties, and simple operation, has become the main method for preparing layered composite materials. However, existing titanium-magnesium rolling composite technologies still have many problems. For example, the rolling method of sandwiching an aluminum plate between a titanium plate and a magnesium plate increases the success rate of bonding, but it is easy to generate intermetallic compounds of titanium-aluminum and magnesium-aluminum, which leads to a decline in material properties. The rolling method of fixing the titanium plate and magnesium plate together with rivets, iron wires, etc., is prone to problems such as unevenness of rolled samples, poor bonding performance, and impurities and pores at the interface. Summary of the Invention

[0004] To address the problems of uneven material distribution, poor bonding leading to poor plasticity, and numerous defects and impurities at the interface in the preparation technology of titanium-magnesium layered composite metal materials mentioned above, this invention provides a titanium-magnesium layered composite metal material and its preparation method.

[0005] The method for preparing the titanium-magnesium layered composite metal material according to the present invention includes the following steps: S1, pretreating pure titanium plates and magnesium alloy plates respectively; S2, alternately stacking pure titanium plates and magnesium alloy plates to form a stacked structure with pure titanium plates as the outermost layer; S3, hot-pressing the stacked structure at a temperature of 500℃ to 600℃ and a pressure of 5MPa to 20MPa to form a pre-bonded block; S4, rolling the pre-bonded block at a temperature of 400℃ to 500℃ to form a composite structure; S5, annealing the composite structure at a temperature of 350℃ to 500℃ to form the titanium-magnesium layered composite metal material.

[0006] In a preferred embodiment, in step S1, the pretreatment includes pickling and ultrasonic cleaning of the pure titanium plate with anhydrous ethanol, and grinding of the magnesium alloy plate with a wire brush and ultrasonic cleaning with anhydrous ethanol.

[0007] In a preferred embodiment, in step S3, the laminated structure is wrapped in packaging paper and placed in a mold. The mold is then placed in a vacuum hot press furnace and sintered under heat and pressure for 0.5h to 2h. After cooling to room temperature in the furnace, the pre-bonded block is removed to obtain the pre-bonded block.

[0008] In a preferred embodiment, a vacuum is first drawn, then an inert gas is introduced to expel the air, and then a vacuum is drawn again to ensure that there is no residual air in the furnace. After the vacuum is drawn, the vacuum degree in the furnace is maintained at 0.01 Pa, and then the temperature and pressure are increased.

[0009] In a preferred embodiment, the heating and pressurization process includes: setting an initial pressure of 1 MPa to 3 MPa to ensure close contact between the pure titanium plate and the magnesium alloy plate; controlling the heating rate at 10 °C / min; starting uniform pressurization when the temperature reaches 300 °C to 400 °C; ensuring the pressure reaches 5 MPa to 20 MPa when the temperature reaches 500 °C to 600 °C; and then holding the temperature and pressure at 500 °C to 600 °C for 0.5 h to 2 h for sintering.

[0010] In a preferred embodiment, in step S4, the pre-bonded block is placed in a muffle furnace for preheating treatment before rolling, and then the composite structure is obtained after 5 to 11 rolling passes.

[0011] In a preferred embodiment, the total reduction rate is 25% to 55%, the single reduction rate is 4% to 10%, and the rolling speed is 0.3 m / s to 0.5 m / s.

[0012] In a preferred embodiment, in step S5, the muffle furnace is heated to 350°C to 500°C, the composite structure is placed in the muffle furnace for annealing, and then cooled to room temperature with the furnace to obtain a titanium-magnesium layered composite metal material.

[0013] In a preferred embodiment, the annealing temperature is 350℃~500℃, and the holding time is 60min~120min.

[0014] The titanium-magnesium layered composite metal material obtained by the above preparation method according to the present invention comprises alternating layers of pure titanium and magnesium alloy.

[0015] The present invention produces a titanium-magnesium layered composite metal material by alternating lamination, vacuum hot pressing and hot rolling of pure titanium plate and magnesium alloy plate. It has high plasticity, long service life, good density and no obvious brittle intermetallic compounds at the interface. Attached Figure Description

[0016] Figure 1 This is an interfacial bonding morphology diagram of the titanium-magnesium layered composite metal material according to Embodiment 1 of the present invention.

[0017] Figure 2 This is an element diffusion diagram at the interface of the titanium-magnesium layered composite metal material according to Embodiment 1 of the present invention. Detailed Implementation

[0018] The preferred embodiments of the present invention are given below with reference to the accompanying drawings and described in detail.

[0019] The method for preparing the titanium-magnesium layered composite metal material according to the present invention first includes providing a pure titanium plate and a magnesium alloy plate. In a preferred embodiment, the pure titanium plate is a TA1 pure titanium plate. In a preferred embodiment, the magnesium alloy plate is a MgAlZn-based magnesium alloy. In a preferred embodiment, the magnesium alloy plate is an AZ31B magnesium alloy plate. In a preferred embodiment, the dimensions of both the pure titanium plate and the magnesium alloy plate are 75 mm in length × 75 mm in width × 0.2 mm in thickness. In a preferred embodiment, the thickness ratio of the pure titanium plate to the magnesium alloy plate is 1:1. In a preferred embodiment, the length-to-width ratio of both the pure titanium plate and the magnesium alloy plate is 1:1.

[0020] The method for preparing the titanium-magnesium layered composite metal material according to the present invention further includes pretreating a pure titanium plate and a magnesium alloy plate respectively. In a preferred embodiment, the pretreatment includes acid washing and ultrasonic cleaning with anhydrous ethanol on the pure titanium plate. In a preferred embodiment, the acid is a 10-15 vol.% HF solution. The pure titanium plate is cleaned with HF solution for 0.5 min to 2 min, and the cleaned pure titanium plate is silvery-white. In a preferred embodiment, the pretreatment includes wire brush polishing and ultrasonic cleaning with anhydrous ethanol on the magnesium alloy plate. In a preferred embodiment, the polished magnesium alloy plate is silvery-white. In a preferred embodiment, HF solution cleaning and wire brush polishing are used to remove impurities such as oxidation and oil stains from the surfaces of the pure titanium plate and the magnesium alloy plate, respectively. Then, the pure titanium plate and the magnesium alloy plate are placed in anhydrous ethanol solution for ultrasonic cleaning for 10-15 min and dried to expose fresh metal.

[0021] The method for preparing the titanium-magnesium layered composite metal material according to the present invention further includes alternately stacking pure titanium plates and magnesium alloy plates to form a stacked structure with the pure titanium plate as the outermost layer. In a preferred embodiment, the pure titanium plates and magnesium alloy plates are alternately stacked in a titanium-magnesium-titanium...magnesium-titanium-magnesium-titanium manner. In a preferred embodiment, there are N magnesium alloy plates and N+1 pure titanium plates. In one preferred embodiment, 13 pure titanium plates and 12 magnesium alloy plates are stacked in a titanium-magnesium-titanium...magnesium-titanium-magnesium-titanium manner to form a stacked structure of 25 layers.

[0022] The method for preparing the titanium-magnesium layered composite metal material according to the present invention further includes hot-pressing the laminated structure at a temperature of 500°C to 600°C and a pressure of 5 MPa to 20 MPa to form a pre-bonded block. Specifically, 500°C to 600°C is below the melting point of magnesium, ensuring the bonding of titanium and magnesium while controlling the material forming, resulting in a dense pre-bonded block free of oxides, oil stains, and other impurities at the interface and without voids. In a preferred embodiment, the laminated structure is wrapped in packaging paper and placed in a mold. The mold is then placed in a vacuum hot press furnace and sintered under heat and pressure for 0.5 h to 2 h. After cooling to room temperature in the furnace, the pre-bonded block is obtained. In a preferred embodiment, the packaging paper is graphite paper. It should be understood that other materials with good thermal conductivity, high temperature resistance, and ease of demolding can also be used in this invention. In a preferred embodiment, the mold is a metal mold. It should be understood that molds made of other materials with good compressive strength and thermal conductivity can also be used in this invention. In a preferred embodiment, a vacuum is first drawn, then inert gas is introduced to purge the air, followed by another vacuum to ensure no residual air remains in the furnace. After vacuuming, the vacuum level inside the furnace is maintained at 0.01 Pa before heating and pressurization. In a preferred embodiment, the heating and pressurization process includes: setting an initial pressure of 1 MPa to 3 MPa to ensure tight bonding between the pure titanium plate and the magnesium alloy plate; controlling the heating rate at 10 °C / min until the hot-pressing temperature of 500 °C to 600 °C is reached; during the heating process, uniform pressurization begins when the temperature reaches 300 °C to 400 °C, so that the pressure reaches 5 MPa to 20 MPa when the temperature reaches 500 °C to 600 °C; subsequently, sintering is carried out at 500 °C to 600 °C for 0.5 h to 2 h. In a preferred embodiment, the pre-bonded interface of the pre-bonded block is good, flat, and free of impurities and pores.

[0023] The method for preparing the titanium-magnesium layered composite metal material according to the present invention further includes rolling a pre-bonded block at a temperature of 400°C to 500°C to form a composite structure. Specifically, the temperature of 400°C to 500°C ensures that the material softens for easy processing and prevents spontaneous combustion of the magnesium alloy, thereby improving the success rate of composite structure preparation. In a preferred embodiment, the rolls are cleaned before rolling to prevent oxides on the rolls from adhering to the composite plate and affecting rolling uniformity. In a preferred embodiment, the pre-bonded block is placed in a muffle furnace for preheating treatment before rolling, and then the composite structure is obtained through 5 to 11 rolling passes. In a preferred embodiment, the preheating temperature is 400°C to 500°C, and the preheating time is 5 min to 10 min. In a preferred embodiment, the total reduction rate is 25% to 55%, the single reduction rate is 4% to 10%, and the rolling speed is 0.3 m / s to 0.5 m / s. In a preferred embodiment, the intermediate heating temperature for multi-pass hot rolling is 400℃~500℃, and the intermediate heating time for multi-pass hot rolling is 5min~10min. In particular, by employing multi-pass hot rolling technology, the rolling pressure and rolling speed of each pass are controlled to ensure the uniformity and bonding strength of the two metal sheets, and to avoid phenomena such as material breakage, delamination, and unevenness.

[0024] The method for preparing the titanium-magnesium layered composite metal material according to the present invention further includes annealing the composite structure at a temperature of 350°C to 500°C to form the titanium-magnesium layered composite metal material. In a preferred embodiment, the composite structure is placed in a muffle furnace at 350°C to 500°C for annealing, and then cooled to room temperature with the furnace to obtain the titanium-magnesium layered composite metal material. In a preferred embodiment, the annealing temperature is 350°C to 500°C, and the holding time is 60 min to 120 min. In particular, the titanium-magnesium layered composite metal material exhibits good bonding at the interface and possesses superior mechanical properties such as high plasticity and long service life compared to single-phase pure titanium or magnesium alloys, combining the advantages of both materials, such as lightweight, corrosion resistance, and strong plastic deformation ability.

[0025] Thus, this invention solves the technical problem of compositing pure titanium plates and magnesium alloy plates by combining vacuum hot pressing and multi-pass hot rolling, and prepares a titanium-magnesium composite metal material with high plasticity, long service life, good density and no obvious brittle intermetallic compounds at the interface.

[0026] Example 1

[0027] The oxidation, oil stains and other impurities on the surface of the pure titanium plate and magnesium alloy plate were removed by cleaning with 10 vol.% HF solution and grinding with a wire brush, respectively. Then the metal plate was placed in anhydrous ethanol solution for ultrasonic cleaning for 15 minutes and blown dry to obtain metal plates with no oxides on the surface and fresh metal exposed, which were then used later.

[0028] Thirteen pre-treated pure titanium plates and twelve magnesium alloy plates were combined in an alternating layering manner, with the pure titanium plates on the outermost layer. A total of 25 layers were stacked in a titanium-magnesium-titanium...magnesium-titanium-magnesium-titanium pattern. After being neatly arranged, they were wrapped in graphite paper and placed in a metal mold. The metal mold was then placed in a vacuum hot press furnace. First, a vacuum was drawn, then argon gas was introduced to purge the air, and finally, a vacuum of 0.01 Pa was maintained. An initial pressure of 1 MPa was set to ensure tight bonding between the pure titanium plates and the magnesium alloy plates. The heating rate was controlled at 10℃ / min until the hot pressing temperature of 500℃ was reached. During the heating process, uniform pressure was applied starting at 400℃, so that the pressure reached 8.5 MPa at 500℃. The mixture was then sintered at 500℃ for 1 hour under pressure. Finally, it was cooled to room temperature in the furnace and removed, yielding a well-bonded, smooth, and pore-free titanium-magnesium layered composite metal material.

[0029] The pre-bonded titanium-magnesium layered composite metal material after vacuum hot pressing was placed in a muffle furnace and held at 500℃ for 10 minutes for preheating treatment before rolling. Then, the preheated titanium-magnesium layered composite metal material was subjected to multi-pass hot rolling with a total reduction rate of 40% and a single reduction rate of 4% to 7%. The rolling speed was 0.3 m / s. The heating temperature and time in the middle of the multi-pass hot rolling were the same as those in the preheating. After 8 rolling passes, a well-bonded titanium-magnesium layered composite metal material was obtained.

[0030] The titanium-magnesium layered composite metal material was annealed in a muffle furnace at a temperature of 500℃ for 60 minutes and then cooled to room temperature in the furnace to obtain a titanium-magnesium layered composite metal material with high plasticity and long service life.

[0031] The tensile properties of the titanium-magnesium layered composite metal material were tested according to the requirements of GB / T228.1-2021 Metallic Materials Room Temperature Tensile Test. The results are shown in Table 1. The elongation at break was 27.95%, which is an improvement of 110.94% and 98.5% respectively compared with pure titanium and magnesium alloy plates prepared by the same rolling method. The fatigue properties of the titanium-magnesium layered composite metal material were tested according to the requirements of GB / T26077-2021 Metallic Materials Axial Strain Controlled Fatigue Test. The results are shown in Table 1. The fatigue life of the composite material was 2907 cycles, which is an improvement of 68.52% and 52.75% respectively compared with pure titanium and magnesium alloy plates prepared by the same rolling method.

[0032] like Figure 1 As shown, scanning electron microscopy was used to observe the interface of the composite metal material. The interface showed good bonding, with no impurities, pores, cracks, or other composite problems, indicating that the obtained titanium-magnesium composite metal material has good density and no obvious brittle intermetallic compounds at the interface. Figure 2 As shown, the diffusion of titanium and magnesium at the interface was analyzed using the line scanning function of an energy dispersive spectrometer. It can be seen that the two elements diffused into each other and formed a metallurgical bond.

[0033] Example 2

[0034] The preparation steps in this embodiment are the same as in Example 1, except that the vacuum hot pressing temperature is changed to 550℃ and held for 1 hour. The tensile test and fatigue test conditions remain unchanged. The results are shown in Table 1.

[0035] Example 3

[0036] The preparation steps in this embodiment are the same as in Example 1, except that the vacuum hot pressing temperature is changed to 600℃ and held for 1 hour. The tensile test and fatigue test conditions remain unchanged. The results are shown in Table 1.

[0037] Example 4

[0038] The preparation steps in this embodiment are the same as in Example 1, except that the vacuum hot pressing temperature is changed to 600℃ and held for 1 hour; the reduction rate is 25%, the single reduction rate is 4% to 6%, the total number of rolling cycles is 5, and the tensile test and fatigue test conditions remain unchanged. The results are shown in Table 1.

[0039] Example 5

[0040] The preparation steps in this embodiment are the same as in Example 1, except that the vacuum hot pressing temperature is changed to 600℃ and held for 1 hour; the reduction rate is 55%, the single reduction rate is 4% to 10%, the total number of rolling times is 11, and the tensile test and fatigue test conditions remain unchanged. The results are shown in Table 1.

[0041] Table 1 Results of Mechanical Property Measurement

[0042] The above description is merely a preferred embodiment of the present invention and is not intended to limit the scope of the invention. Various variations can be made to the above embodiments of the present invention. That is, all simple and equivalent changes and modifications made based on the claims and description of this invention fall within the protection scope of the claims of this patent. All aspects not described in detail in this invention are conventional technical content.

Claims

1. A method for preparing a titanium-magnesium layered composite metal material, characterized in that, The preparation method includes the following steps: S1, pre-treated pure titanium plate and magnesium alloy plate respectively; S2, alternating layers of pure titanium plates and magnesium alloy plates to form a stacked structure with the pure titanium plate on the outermost layer; S3. The laminated structure is placed in a vacuum hot press furnace. First, a vacuum is drawn, then an inert gas is introduced to remove the air, and then a vacuum is drawn again to ensure that there is no residual air in the furnace. After the vacuum is drawn, the vacuum degree in the furnace is maintained at 0.01 Pa. The initial pressure is set to 1 MPa to 3 MPa to make the pure titanium plate and magnesium alloy plate fit tightly together. The heating rate is controlled at 10℃ / min. When the temperature reaches 300℃ to 400℃, the pressure is uniformly applied so that the pressure reaches 5 MPa to 20 MPa when the temperature reaches 500℃ to 600℃. Then, the structure is sintered at 500℃ to 600℃ for 0.5h to 2h. After cooling to room temperature with the furnace, the structure is removed to form a pre-bonded block. S4, at a temperature of 400℃~500℃, the pre-bonded block is placed in a muffle furnace for preheating treatment before rolling, and then the composite structure is obtained by rolling 5~11 times. S5, at a temperature of 350℃~500℃, the composite structure is annealed to form a titanium-magnesium layered composite metal material. The prepared titanium-magnesium layered composite metal material has interdiffusion of titanium and magnesium elements between the layers to form a metallurgical bond, and there are no obvious brittle intermetallic compounds at the interface.

2. The preparation method according to claim 1, characterized in that, In step S1, the pretreatment includes pickling and ultrasonic cleaning with anhydrous ethanol on the pure titanium plate, and grinding with a wire brush and ultrasonic cleaning with anhydrous ethanol on the magnesium alloy plate.

3. The preparation method according to claim 1, characterized in that, In step S3, the laminated structure is wrapped in packaging paper and placed into a mold, and the mold is placed in a vacuum hot press furnace.

4. The preparation method according to claim 1, characterized in that, In step S4, the total reduction rate is 25%~55%, the single reduction rate is 4%~10%, and the rolling speed is 0.3m / s~0.5m / s.

5. The preparation method according to claim 1, characterized in that, In step S5, the muffle furnace is heated to 350°C~500°C, the composite structure is placed in the muffle furnace for annealing, and then cooled to room temperature with the furnace to obtain a titanium-magnesium layered composite metal material.

6. The preparation method according to claim 1, characterized in that, The annealing temperature is 350℃~500℃, and the holding time is 60min~120min.

7. A titanium-magnesium layered composite metal material obtained by the preparation method according to any one of claims 1-6, characterized in that, This titanium-magnesium layered composite metal material consists of alternating layers of pure titanium and magnesium alloy.

Citation Information

Patent Citations

  • Light high-strength titanium-magnesium-titanium vacuum rolling composite material

    CN106180186A

  • Multistage layered heterogeneous copper-aluminum composite material and preparation method thereof

    CN116371915A